The ten most beautiful experiments - Johnson, George, 1952 January 20- (New York : Alfred A. Knopf, 2008)
The ten most fascinating experiments in the history of science--moments when a curious soul posed a particularly eloquent question to nature and received a crisp, unambiguous reply. Johnson takes us to those times when the world seemed filled with mysterious forces, when scientists were dazzled by light, by electricity, and by the beating of the hearts they laid bare on the dissecting table. For all of them, diligence was rewarded. In an instant, confusion was swept aside and something new about nature leaped into view. In bringing us these stories, Johnson restores some of the romance to science, reminding us of the existential excitement of a single soul staring down the unknown.--From publisher description.
Galileo : the way things really move -- William Harvey : mysteries of the heart -- Isaac Newton : what a color is -- Antoine-Laurent Lavoisier : the farmer's daughter -- Luigi Galvani : animal electricity -- Michael Faraday : something deeply hidden -- James Joule : how the world works -- A.A. Michelson : lost in space -- Ivan Pavlov : measuring the immeasurable -- Robert Millikan : in the borderland -- Epilogue : the eleventh most beautiful experiment.
Includes bibliographical references and index.
Keywords: Science -- Experiments; Science -- History